Widespread implementation of domestic information technologies is the main vector of import substitution in the field of FinTech - Yu. P. Kishkovich (Вестник университета, 2025)
In modern conditions, the Russian financial technology sector is experiencing an urgent need to eliminate dependence on foreign technologies both in the field of software and in the field of design solutions and hardware. Russian developers have already started activities in this direction, but there are still a large number of unresolved issues that hamper the FinTech sector development. The purpose of the study is to analyze the issues and prospects for domestic information technologies implementation in FinTech. Research methods are analysis and synthesis, scientific abstraction, and processing of an array of Russian authors’ publications in the field of the information technology industry development in the FinTech sector. The material hsd been considered on the basis of large Russian banks cases. The study concludes that the main direction of import substitution in the field of FinTech solutions is the creation of domestic software and reliable and competitive hardware. Those companies that already have positive experience in this area should replicate it, developing and strengthening the domestic information technology industry. In this case, it is necessary to be guided not only by economic effects, but also by social ones. Solving the issue of dependence on foreign software is a matter of competitiveness of the country’s economic system and, consequently, of individual business entities.